2023
DOI: 10.1111/vox.13427
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and outcomes by blood group in trauma patients: A systematic review and meta‐analysis

Abstract: Background and Objectives Blood group O contains lower levels of factor VIII and von Willebrand factor. Higher incidence of bleeding among group O is reported in multiple contexts. Results of studies vary regarding outcomes stratified by blood group in trauma. We systematically reviewed the literature for outcomes related to blood group in trauma patients. Meta‐analysis of studies evaluating mortality related to blood group was performed. Materials and Methods The PubMed and Embase databases were searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…36,37 Recent studies also showed that other features such as gender or type 0 versus nontype 0 blood group in trauma did not significantly change survival after transfusion events. 38,39 As was our aim, we could show that it is possible to predict renal function deterioration using ML. The prediction may be enriched by combining the RR and feature importance analysis in terms of which features to watch out for: RR analysis confirmed that blood age bears no major risk for renal deterioration, whereas elevated creatinine pretransfusion did.…”
Section: Anesthesia and Analgesiamentioning
confidence: 96%
“…36,37 Recent studies also showed that other features such as gender or type 0 versus nontype 0 blood group in trauma did not significantly change survival after transfusion events. 38,39 As was our aim, we could show that it is possible to predict renal function deterioration using ML. The prediction may be enriched by combining the RR and feature importance analysis in terms of which features to watch out for: RR analysis confirmed that blood age bears no major risk for renal deterioration, whereas elevated creatinine pretransfusion did.…”
Section: Anesthesia and Analgesiamentioning
confidence: 96%